Sociometric Risk Network Structure, HIV Prevalence, and Drug Injection-Related Norms among People Who Inject Drugs (PWID) in Athens, Greece. (27th May 2021) - Hadjikou, Andria; Pantavou, Katerina; Pavlitina, Eirini; Pavlopoulou, Ioanna D.; Economou, Mary; Christaki, Eirini; Lamnisos, Demetris; Kostaki, Evangelia-Georgia; Paraskevis, Dimitrios; Schneider, John; Talias, Michael; Friedman, Samuel R.; et al.
Abstract: Background: Structural properties of sociometric networks have been associated with behaviors related to HIV transmission. Very few studies, however, have explored the correlation between sociometric network factors and drug injection-related norms. Methods: This exploratory work: (i) describes basic structural qualities of a sociometric risk network of participants in the Transmission Reduction Intervention Project (TRIP) in Athens, Greece, in the context of a large HIV outbreak among people who inject drugs (PWID); (ii) measures HIV prevalence within specific structures within the sociometric risk network of PWID in TRIP; and (iii) explores the association of structural properties of the sociometric risk network in TRIP with drug injection-related norms. Results: The sociometric risk network in TRIP consisted of a large component ( n = 241, 67.8%), a few small components ( n = 36, 10.1%) with 2-10 individuals each, and some isolates ( n = 79, 22.2%). HIV prevalence was significantly higher in the large component (55.6%), the 2-core (59.1%) and 3-core (66.3%) of the large component, and the 3-cliques of the cores. Drug injection-related norms were significantly associated with structural characteristics of the sociometric risk network. A safe behavioral pattern (use of unclean cooker/filter/rinse water was never encouraged) was significantly ( p = 0.03) less normative among people who TRIP participants of the 2-core injected with (40.5%) than among network contacts of TRIP participants outside the 2-core (55.6%). On the contrary, at drug-using venues, 2-core members reported that safer behaviors were normative compared to what was reported by those without 2-core membership. Conclusions: Sociometric network data can give useful insights into HIV transmission dynamics and inform prevention strategies. Supplemental data for this article is available online at https://doi.org/10.1080/10826084.2021.1914103 .